FORESTS OF UZBEKISTAN - Mavlanov Khudargan , Kodirov Gayrat Uroqbaevich , Kodirova Surayyo (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article provides information on the distribution of species of alfalfa (Alhagi), their economic importance, the current state of the species in Uzbekistan, eco-biological characteristics, methods of reproduction, the creation of artificial alfalfa and ways to radically improve the crisis alfalfa.